2015
DOI: 10.1016/j.cnsns.2014.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of airline alliance route networks

Abstract: The aim of this study is to analyze the robustness of the three major airline alliances' (i.e., Star Alliance, oneworld and SkyTeam) route networks. Firstly, the normalization of a multi-scale measure of vulnerability is proposed in order to perform the analysis in networks with di↵erent sizes, i.e., number of nodes. An alternative node selection criterion is also proposed in order to study robustness and vulnerability of such complex networks, based on network e ciency. And lastly, a new procedure -the invert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…In general, it was found that major international formed connections that contained distribution tails which were orders of magnitude higher than the power-law, and budget airlines formed connections that had a degree tail distribution which was poorly connected, indicating a Pauper effect. The robustness [35] of the air transport network subject to random removal was tested in [4,9,10,32], and it was found that the existing network structure has been designed for efficiency and is not resilient against failures or attacks.…”
Section: Mesoscopic Network Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it was found that major international formed connections that contained distribution tails which were orders of magnitude higher than the power-law, and budget airlines formed connections that had a degree tail distribution which was poorly connected, indicating a Pauper effect. The robustness [35] of the air transport network subject to random removal was tested in [4,9,10,32], and it was found that the existing network structure has been designed for efficiency and is not resilient against failures or attacks.…”
Section: Mesoscopic Network Propertiesmentioning
confidence: 99%
“…Both global and regional studies have explored their complex network structure across different network scales [5][6][7] with multilayer analysis [6,8]. The analysis predominantly focus on robustness from attacks or failures [9,10], efficiency [4], and structural evolution [7]. The air transportation network is also responsible for the propagation of knowledge and culture [11], infectious diseases [12][13][14][15][16], and understanding the network properties allows scientists to better estimate the intangible benefits and risks of global transportation.…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of metrics have been used to identify the most important nodes for removal, but degree and betweenness remain the most prolific concepts [41,56]. Nie et al [41] and Lordan et al [37] show examples of strategies that cleverly combine different metrics to create more effective disruption strategies. Link betweenness is the most commonly used metric when removing links, although Pu and Cui [46] give an example that uses another metric (longest path) to effectively disturb a network.…”
Section: Vulnerability In Hub Networkmentioning
confidence: 99%
“…The global air transport network is another example where the application of complex network theory has greatly advanced the understanding of network dynamics and has promoted the study of vulnerability [34][35][36][37]42]. Maritime and air transport networks are parallel in many ways.…”
Section: Introductionmentioning
confidence: 99%
“…First, they imply that any simulation performed to understand the dynamics of the system may yield misleading results when the multi-layer structure created by airlines is neglected. In spite of this, most of the recent research works in this fields fail to include this essential ingredient, both in the analysis of delay propagation [23,24] and of the network robustness to disruption and attacks [25,26,27]. Second, it has to be noticed that the air transport system is created by the interactions between a large number of agents, which may create different layers along different dimensions.…”
Section: Discussionmentioning
confidence: 99%